Description of HIV risk behavior among adolescent female sex workers: Findings from the nationwide cross-sectional integrated biological and behavioral surveillance (IBBS) 2014–15 survey for HIV in India - Sanjay K. Rai; Nishakar Thakur; Shreya Jha; Pradeep Kumar; Partha Haldar; Shashi Kant; Puneet Misra; Srinivas Venkatesh (Journal of Family Medicine and Primary Care)
Introduction: Adolescent female sex workers are at high risk of acquiring human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) infection. There was paucity of information regarding their sexual practices. The main objective of this study was to study the sexual behavior, condom use practices, and physical and sexual violence experienced by adolescent female sex workers (FSWs). Materials and Methods: This study was a secondary data analysis of the data collected during the nationwide IBBS 2014–15 survey. All adolescent FSWs aged 15 to 19 years were included in the analysis. The primary outcome variable was HIV serostatus, and independent variables included sexual behavior and condom use practices and socio-demographic variables. Descriptive analyses were performed to estimate the prevalence of independent variables. Ethical approval of the original IBBS study was obtained by the Ethics Committee of National AIDS Control Organization. Results: A total of 948 adolescent FSWs were included in the final analysis. The prevalence of HIV in adolescent FSWs was 1.2% [95% confidence interval, 0.1–1.9%]. The mean age [standard deviation (SD)] of FSWs was 18.2 (0.9) years. The mean (SD) age at first sexual intercourse was 15.6 (1.7) years, and the mean (SD) age of starting sex work was 16.6 (1.5) years. The majority of the FSWs (94%) had used condom during the last sexual intercourse with a commercial partner, and about one-thirds (66%) had consistently used condom with a commercial partner. About a quarter (26%) of the FSWs had anal intercourse with a commercial partner in the last 1 month. About one in five FSWs (21%) had experienced physical violence in the last 1 year. Conclusion: Almost one-third of FSWs had high-risk sexual behavior like multiple clients, anal intercourse, inconsistent condom use, and so on. These behaviors in turn increase their vulnerability to HIV infection.